2010
DOI: 10.1093/aje/kwq143
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic Endometriosis Diagnosed in an Entire Nation Over 20 Years

Abstract: The annual incidence of pelvic endometriosis among women aged 15-49 years and up to age 69 years was ascertained for the Icelandic population between 1981 and 2000 by using Iceland's extensive record linkage systems. Comprehensive, state-financed health care and unique personal identification numbers enabled care to be tracked from first diagnosis. To identify cases, a centralized discharge-code registry was searched, as well as all hospital databases and, for individual patients, all hospital records. Each ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
93
1
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(114 citation statements)
references
References 16 publications
16
93
1
4
Order By: Relevance
“…32 The characteristics of our trial population of premenopausal women with endometriosis were similar to those of patients in epidemiologic studies of endometriosis and chronic pelvic pain. [37][38][39] The safety and efficacy results of Elaris EM-II confirmed the results of Elaris EM-I, which showed the internal validity. The two trials were limited by the entry criteria and length of the intervention period.…”
Section: Discussionsupporting
confidence: 61%
“…32 The characteristics of our trial population of premenopausal women with endometriosis were similar to those of patients in epidemiologic studies of endometriosis and chronic pelvic pain. [37][38][39] The safety and efficacy results of Elaris EM-II confirmed the results of Elaris EM-I, which showed the internal validity. The two trials were limited by the entry criteria and length of the intervention period.…”
Section: Discussionsupporting
confidence: 61%
“…Endometriosis is one of the leading causes of infertility in women of reproductive age (Ayala and Mota, 2007). Our results showed that 71% of the patients were <35 years old, which is consistent with the findings of other international reports showing that the incidence of endometriosis is higher in women of reproductive age (Gylfason et al, 2010).…”
Section: Discussionsupporting
confidence: 93%
“…Here, we showed that 71% of our patients were <35 years old, which is consistent with other international reports showing that the incidence of endometriosis is higher in women of reproductive age [33]. When we adjusted the study groups according to family history of endometriosis, we observed that 7% (10/151) of patients had a positive history of familial endometriosis (mother or sister).…”
Section: Discussionsupporting
confidence: 91%